Synthesis and Crystal Structure of 3D Network Barium(II) Complex with Succinic Acid - Liu, Xia; Dong, Hua-Ze; Pi, Zong-Xin; Bi, Jian-Hong (Asian Journal of Chemistry, 2013)
A new dimensional alkaline-earth metal-organic framework complex, [Ba(L)]n (L = succinic acid) (1), has been synthesized by hydrothermal method and characterized by single crystal X-ray diffraction studies. Structural determination reveals that the coordinated geometry of Ba is a capped distorted pentagonal bipyramidal geometry. Each metal ion is coordinated by eight O from six different carboxylate groups. While each succinate acid ligand coordinates six alkaline earth metal centers to form 3D network.